2013
DOI: 10.1002/fuce.201200040
|View full text |Cite
|
Sign up to set email alerts
|

A PFSA Composite Membrane with Sulfonic Acid Functionalized TiO2 Nanotubes for Polymer Electrolyte Fuel Cells and Water Electrolysers

Abstract: Titanate nanotubes (TiO2‐NT) were functionalized with sulfonic acid functional groups and characterized with Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X‐ray diffraction (XRD). Results confirmed that sulfonic acid groups were grafted onto TiO2‐NT with a uniform distribution. When the functionalized titanate nanotube (F‐TiO2‐NT) was incorporated in perfluorosulfonic acid membranes, the membrane conductivity and water uptake wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…XRD analysis of the nanotube samples, before and after heattreatment, clearly indicated that the crystal structure changed to anatase TiO 2 (see Supplementary information for further detail) in agreement with the published literature [30][31][32]. The aggregates of TiO 2 nanotubes exhibited a mesoporous structure, in which Au nanoparticles could be incorporated into the scaffold.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…XRD analysis of the nanotube samples, before and after heattreatment, clearly indicated that the crystal structure changed to anatase TiO 2 (see Supplementary information for further detail) in agreement with the published literature [30][31][32]. The aggregates of TiO 2 nanotubes exhibited a mesoporous structure, in which Au nanoparticles could be incorporated into the scaffold.…”
Section: Resultssupporting
confidence: 85%
“…TiO 2 nanotubes were prepared by the alkaline hydrothermal treatment method [29][30][31][32][33]. Briefly, anatase TiO 2 nanopowders (1.2 g) were dispersed in of 10 mol dm À 3 NaOH solution (100 cm 3 ) with ultrasonication.…”
Section: Synthesis Of Tio 2 Nanotubes and Au Nanoparticlesmentioning
confidence: 99%
“…Among the metal oxides, one of the most widely researched materials is silicon oxide. Other common metal oxides used for this purpose include TiO 2 [43,44], ZrO 2 [45] and Fe 3 O 4 [46]. Adjemian, [21] et al [47] introduced hydrated SiO 2 (via sol-gel method) in the Nafion hydrophilic channels to improve the water retention for use in a PEFC above 100 °C.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…Based on above, hydrophilicity and antifouling ability of membrane surface can be enhanced due to minimization of mass transfer resistance between the semi-conductor surface and fluid bulk via the forced transport of reactants by convection [5]. Great variety of materials has been used for the membrane surface modification, such as TiO 2 nanotubes [6], TiO 2 -graphene oxide (GO) [7][8][9], carbon nanotubes (CNTs) [10][11][12][13], etc.…”
Section: Introductionmentioning
confidence: 99%